Ganesh: um grupo de extensão para ensino de Segurança da Informação do ICMC/USP - Salles, Felipe Mendes; Marinho, Emelly; Cruz, Gabriel; Scarpin, Renan Parpinelli; Branco, Kalinka (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
This article describes the methodology of Ganesh, an extracurricular group at the University of São Paulo (USP) São Carlos, dedicated to promoting knowledge about Information Security among undergraduate students and the technology community. Ganesh began in 2010 as part of a university outreach project that, over the past few years, has developed teaching materials, specialized courses, and workshops, in addition to creating educational projects for public and private schools. Ganesh connects with the public through various outreach initiatives, including their YouTube channel, an annual selection process (PING), and participation in Capture the Flag (CTF) competitions. Using a methodology that combines hands-on learning, challenge solving, and weekly meetings has positioned them among the top teams in Brazil and among the country’s top university teams in the best Information Security competitions.